Uma investigação sobre o uso da UML Statechart para representar o comportamento de aplicações modeladas em Matlab/Simulink - Freire, Guilherme Mendonça (2011)
Embedded systems (ES) has become more important to everyday life due to technology advance and increasing application field. Engineers start ES development using tools like Matlab/Simulink. Usually, Simulink models are low level abstraction models following an ad-hoc design, which difficult the model comprehension. Hence, new trends start to apply software engineering to support ES design. Goal: This work was developed in a research group that is defining a development process to support ES development from initial phases to Simulink models implementation. Particularly, this works goal is to explore UML Statchart technique to depict Simulink models in a high level abstraction view, and become the group s desired component part of the process. Method: The investigation process was conducted in three actions exploring UML Statchart based in the Research Action methodology: (i) a reengineering activity starting from Simulink model; (ii) a forward engineering starting from a requirement document; and (iii) a survey investigating the use of UML Statechart by ES developers. Outcomes: The first and second action showed that UML Statechart is an appropriated technique to depict the application behavior, contributing to implement Simulink models. It also organizes Simulink models and facilitates the system comprehension as a whole. Conclusion: Due to the conducted actions outcomes, UML Statechart can be considered as a candidate to compose one of the artifacts to be implemented during the process that is being defined by the research group. However, this work conducted investigations are limited to two system applications, needing to accomplish more complement studies, we can say that Simulink models implemented with support of UML Statechart, are better structured and more comprehensive. This features an increasing quality in ES design.